A field experiment to determine the effect of post‐fire salvage on seedbeds and tree regeneration. Issue 2 (1st March 2006) - Greene, David F.; Gauthier, Sylvie; Noël, Joseé; Rousseau, Mélanie; Bergeron, Yves
Abstract : In North America, Eurasia, and Australia, salvage logging is increasingly being used to mitigate economic losses due to fire, although the effects of this type of intervention are still essentially unknown. In a field experiment in a large recent boreal forest fire in central Quebec, we used 24 paired salvaged and non‐salvaged stands to test the effect of salvage on the recruitment of two conifer species possessing an aerial seed bank (Pinus banksiana andPicea mariana ). The seedbeds following salvage were, on average, more hospitable to germination, but, incongruously, engendered far lower regeneration densities. The poor recruitment on salvaged sites was due primarily to the loss of seeds following the immediate post‐fire salvage, when cone‐bearing branches were removed along with the trunks. By contrast, the density of the asexually‐recruitedPopulus tremuloides was relatively unaffected. We suggest simple ways to modify current salvage procedures that would retard this transition from conifer toPopulus forest, as well as leaving more wood in situ.